Learning theories in childhood - Gray, Colette; MacBlain, Sean (SAGE, 2015)
Focusing on the early philosophies of learning and key behavioural, cognitive, and social theorists, including Locke, Rousseau, Montessori, Piaget, Vygotsky, Bandura, Bronfenbrenner and Bruner, this popular book provides a comprehensive overview of children's learning.